Determination of the severity grade of diffuse lung atelectasis in preterm infants with extremely low birth weight by x-ray data - Вороньжев, Ігор Олександрович; Сорочан, Олексій Павлович (ScienceRise: Medical Science, 2016)
The aim of our research is in improvement of diagnostics of diffuse lung atelectasis (DLA) in preterm infants with extremely low body weight by X-ray data by the way of objectivization of its severity grade. Methods of research: We analyzed the data of X-ray photographs of breast organs (BO) of 13 preterm infants with extremely low body weight that DLA was diagnosed in. Among them were 8 boys and 5 girls. X-ray photographs of 15 children with extremely low body weight without DLA were studied as the group of comparison. Results: Statistical analysis of the data that characterized DLA in preterm children with extremely low body weight was carried out. At the study of X-ray photographs of BO of the control group, there were not detected the focal shades along the lung fields, diaphragm cupolas were placed not higher than 6 rib and cardiothoracic index did not exceed 55. In studied group the prevalence of focal shades up to the one third of lung field was observed in 2 children (15,38 %), up to two thirds of lung field– 5 preterm infants (38,46 %) and along all lung fields in 6 children (46,15 %). The displacement of right cupola of diaphragm to the 6 rib was observed in 3 children (23,08 %), to the level of 5 rib – 4 children (30,77 %), to the level of 4 rib and higher – 6 children (46,15 %). Cardiothoracic index within 55-57 was observed in 4 preterm infants (30,77 %), in 5 children (38,46 %) index was 58-60 and in 6 children exceeded 61. Conclusion: The researches allowed divide the diffuse lung atelectasis in preterm infants with extremely low body weight in three severity grades by X-ray data